PENEGAKAN HUKUM TINDAK PIDANA CYBERPORN DI APLIKASI MEDIA SOSIAL BIGO LIVE: STUDI DI DITRESKRIMSUS POLDA JATIM - Elvaretta Helsa Salsabilla; Ahmad Mahyani (Gapenas Publisher, 2022)
The development of internet technology at this time is one of the most popular ones, especially among teenagers. But not a few of them make the internet a new means to commit crimes against decency, namely cyberporn crimes. Cyberporn is a form of pornography that can be accessed online through an internet network. Enforcement of cyberporn criminal acts is regulated in the Law of the Republic of Indonesia Number 11 of 2008 Jo Law Number 19 of 2016 concerning Electronic Information and Transactions; Law No. 44 of 2008 concerning Pornography and the Criminal Code on Pornography. The problems studied in this study are: (1) How to expand the meaning of pornography in the Bigo Live social media application. (2) How to prevent cyberporn crimes on social media based on live streaming video. The research methods used are qualitative approaches and types of sociological juridical or empirical juridical research. Data obtained by conducting interviews, literature studies and questionnaires. The results of the research from this study are: (1) The importance of the role of law enforcement officials in conducting law enforcement in Indonesia in cyberporn crimes based on live streaming video. (2) Efforts to prevent cyberporn crimes that are rife on the Bigo Live application and by using criminal policies so that they do not happen again with other cases and make the public even more aware of cyberporn crimes. The conclusion of this study is (1) Abuse in the Bigo Live application which still has a lot of content containing pornographic elements has violated the ITE Law, the Pornography Law and the Criminal Code and because there are still many misinterpreters, a Joint Decree on Implementation Guidelines for certain articles in the ITE Law (2) Prevention efforts carried out for cyberporn crimes by carrying out criminal policies using two paths, namely penal facilities and non-piration facilities